A Review of the Utilisation of Recycled Waste Material as an Alternative Modifier in Asphalt Mixtures - Milad, Abdalrhman Abrahim; Ali, Ahmed Suliman B.; Yusoff, Nur Izzi Md (Civil Engineering Journal, 2020)
The possibility of using waste materials in road construction is of great interest as their utilisation may contribute to reducing the problems of hazard and pollution and conserve natural resources. Thus, there is an urgent need to find a sustainable method for using waste materials as a substitute in the standard asphalt binders. There are several concerns about the physical and chemical properties and mechanical performance of asphalt pavements incorporated with waste material in the effort to reduce permanent deformation of the road surface. This review article presents a brief discussion of the asphalt mixtures modified with waste material, and the recycled materials used as a modifier in the asphalt mixture. The present paper summarises the use of crumb rubber, crushed concrete, steel slag, glass fibre and plastic waste in asphalt mixtures. The use of waste materials as a modifier in asphalt mixture resulted in improved asphalt pavement performance. Results advocate that rubberised asphalt mixture with desired properties can be designed as an additive with a friendly environmental approach in construction materials. The researches that adopted the influence of usage, recycle waste material to improve the performance of the asphalt of the road are still limited compared to other construction fields.Â Doi: 10.28991/cej-2020-SP(EMCE)-05 Full Text: PDF